THE TRANSFORMATION OF CHRISTOLOGICAL CODES IN KATERYNA KALYTKO’S WORK «WHEN THEY BROUGHT HIM TO THE AID STATION – IT RESEMBLED THE PIETÀ» - Senkiv, Mykhailo (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2026)
This article analyses Kateryna Kalytko’s poem ‘When They Brought Him to the Aid Station – It Resembled the Pietà’ through the prism of Christian imagery and its hermeneutic interpretation. The central focus is the first line of the poem, which opens up a multi-layered space for interpretation: from canonical biblical history to contemporary wartime experience. The poem emerges as a sacred space where the symbolism of blood, water and light transforms traditional Gospel motifs into an experience of sacrifice and salvation. The use of Hans-Georg Gadamer’s concepts of the ‘flash’ and the hermeneutic triad of understanding, interpretation and articulation allows us to define the poetic word as a metaphysical instrument for the creation of meaning. Comparisons with Michelangelo’s ‘Pieta’ and intertextual parallels with the Gospel highlight the richness of Kalytko’s artistic imagery. In this context, poetry emerges as a modern Gospel, where the body of a wounded warrior takes on a new form of existence, and suffering opens up the possibility of spiritual resistance even in a state of abandonment by God.